Carbon Dioxide Emission Management in Power Generation - Nord, Lars O; Bolland, Olav (John Wiley & Sons, Incorporated, 2020)
Provides an engaging and clearly structured source of information on the capture and storage of CO2 Designed to bridge the gap between the many disciplines involved in carbon dioxide emission management, this book provides a comprehensive yet easy-to-understand introduction to the subject of CO2 capture.